Monitoring fatigue in trained soccer players during specific workouts - Del Aguila Ruiperez, A.; Castano, A.; Martinez, A. I.; Capelo, F.; Penalver, A.; Jimenez Reyes, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Soccer is a complex sport requiring the repetition of many different activities such as jogging, sprinting and jumping (Bloomfield et al, 2007). The combination, managing and adjusting of these activities is essential in order to organize the well known "Small Side Games" (SSG). Besides, the ability to sprint is a key parameter (Faude et al 2012) and is the most frequent action in goal situations. To our knowledge, no one date has examined the influence of repetition of SSG sequences, neither if the degree of fatigue due to the accumulation of actions performed is associated with simple mechanical parameters related to fatigue. Thus, the aims of this study were: 1) to investigate relationships between mechanical parameters related to jump and maximal sprint running before and after a specific SSG, and 2) to quantify changes in these data due to fatigue induced by SSG. Methods: Sixteen trained soccer players performed a maximal sprint of 30-m before the specific SSG. Instantaneous running velocity (v in m·s-1) over time and distance was recorded with a radar Stalker ATS SystemTM (Radar Sales, Mineapolis, MN, US). As well, a countermovement jump (CMJ) and a standing long jump (SLJ) were performed before the SSG. The SSG was composed by 4 repetitions of: a straight sprint over 15-m (without ball), a change of direction and 15-m of 2-on-1 situation finishing with a shot. Immediately after the SSG, players performed a 30-m maximal sprint, CMJ and SLJ in order to check the decrease in performance. Results: CMJ height and SLJ performance loss pre-post SSG were highly significant and were strongly correlated (r = 0.86; p<0.001). The speed losses produced by the specific SSG presented a high relation with CMJ and SLJ exercises (r = 0.77 - 0.88; p<0.001). Besides, top speed and the moment which is achieved in the maximal sprint running significantly decreased (p<0.001). Discussion: The high correlations found between mechanical responses (speed, CMJ height and SLJ performance losses) and the marked alterations observed in this study during a specific SSG, could be useful as indicators of fatigue and this could highlight the utility and validity of using CMJ and SLJ to monitor training load in different specific workouts, as has been proposed by Jiménez-Reyes et al (2013) in other activities. Such data would provide new information on the mechanical manifestation of fatigue during specific SSG sequences, which would then be used to design optimal training routines to improve players`s training session.